Prevalence of needle stick injuries, its associated factors and awareness among nursing staff at tertiary care hospital of North India - Bharti, Prem Prakash; Singh, Naresh Pal; Bajpai, Prashant Kumar; Rani, Vidya; Jain, Pankaj Kumar; Khan, Ayub (Indian Journal of Community Health, 2022)
Background: Needle Stick Injuries (NSIs) are defined as accidental skin penetrating injuries caused by needles. It is the single greatest occupational hazard to a medical personnel. In developing countries, needle stick injury is associated with the highest global prevalence of HIV, Hepatitis B, and Hepatitis C. Aim & Objectives: To estimate the prevalence of needle stick injuries, its associated risk factors and assess the awareness regarding needle stick injuries among nursing staff. Material & Methods: A cross-sectional study was conducted among nursing staff who were working at a tertiary care hospital in Northern India during June 2019 to November 2019. The study commenced after taking prior approval from institutional ethics committee. A census method was used to include the participants. Results: Around 66.7% of the nursing staff was exposed to NSIs during their working hours at the hospital. There was significant association of needle stick injuries with place of working and education of nursing staff in multivariate binary logistic regression. About 26% of the nurses were unaware that recapping should be done or not for used needle, and 35% of staff nurses recapped the needle after the use. Conclusion: Needle stick injuries can be prevented by continued education, effective training, providing better safety devices, a positive work environment.